ASPEK KRIMINOLOGI TERHADAP TINDAK PIDANA MENGALIHKAN OBJEK JAMINAN FIDUSIA TANPA PERSETUJUAN TERTULIS TERLEBIH DAHULU DARI PENERIMA FIDUSIA BERDASARKAN PUTUSAN PENGADILAN NEGERI TANJUNGKARANG NOMOR : 740/PID.SUS/2020/PN.TJK - Tami Rusli; Yulia Hesti; Heru Andrianto (Fakultas Hukum Universitas Tulang Bawang, 2022)
A person in a consumer financing agreement with a fiduciary guarantee is prohibited from transferring the object of the fiduciary guarantee to another party without the consent of the fiduciary recipient. This study discusses the problem of what are the factors causing the perpetrator and how criminal responsibility for the perpetrator of a criminal act transfers the object of the fiduciary guarantee without prior written consent from the fiduciary recipient. This study uses a normative juridical approach and an empirical juridical approach. Collecting data by field studies and literature studies. Data analysis was carried out in a qualitative juridical manner, namely the analysis was carried out descriptively. Consumer finance companies should control, supervise and review the object of fiduciary security every month so that it can be seen whether the object of the fiduciary guarantee is in the control of the debtor, is not damaged and is not transferred to a third party, thereby reducing the losses that will be suffered by the creditor and is expected to be necessary. there is awareness of the public who enter into consumer financing agreements with fiduciary guarantees to pay more attention to their responsibilities in fulfilling achievements, because acts of breach of contract cannot always be resolved by deliberation. The imposition of imprisonment if it can provide a deterrent effect and become a motivation for good intentions. Keywords : Criminal Liability, Criminal act, Fiduciary Guarantee